A109 PREGNANCY OUTCOMES IN WOMEN EXPOSED TO USTEKINUMAB IN THE CROHN'S DISEASE CLINICAL DEVELOPMENT PROGRAM. (1st March 2018) - Scherl, E; Jacobstein, D; Murphy, C; Ott, E; Gasink, C; Baumgart, D C; Abraham, B
Abstract: Background: Ustekinumab (UST) has been approved for moderate to severe Crohn's Disease (CD) in adult patients (pts). While no adverse developmental outcomes (pre-& postnatal) were observed in animal studies of UST, limited data exist, including previously reported outcomes in psoriasis (PsO) pts, concerning the effects of UST on human pregnancies 1 . Aims: To characterize pregnancy outcomes in women exposed to UST during pregnancy, data from the UST CD clinical development program (CDP) are presented. Methods: Pregnancies reported with maternal use of UST (typical terminal half-life of approx 3 weeks) from 5 CD studies were evaluated: 2 Phase 2 (C0379T07:n=131; CERTIFI:n=526) & 3 Phase 3 (UNITI-1:n=769 & UNITI-2:n=640, from which 1, 281 continued on maintenance in IM-UNITI). Results: 877 female pts received ≥1 IV or SC dose of UST, and 26 maternal pregnancies were reported (despite agreeing to adequate birth control). UST treatment was discontinued upon the report of pregnancy in all cases. Mean maternal age was 27.6 years (range 19–43) and mean duration of UST exposure prior to the reported pregnancy was 76 ± 62.1 weeks. Pregnancy outcomes were reported for 24 of 26 pregnancies, including 15 (62.5%) live births (LBs), 4 (16.7%) spontaneous abortions (SAs), and 5 (20.8%) elective abortions. All 4 SAs occurred in the 1 st trimester. Mean maternal age was older for pts who had SAs (33.0 ± 2.94 years) vs. LBs (27.6 ± 3.75 years) and median UST treatment duration was longer for pts who had SAs (80 weeks) vs. LBs (56 weeks). Among the LBs, there were no congenital anomalies; 1 infant had a single episode of transient hypoglycaemia treated with oral supplement. No safety signals emerged with neonatal outcomes with gestational age of 38.2 ± 1.3 weeks (n=12), mean 5 min-APGAR of 9.8 ± 0.45 (n=5), and mean birth weight of 6.6 ± 1.6 pounds (n=13). Conclusions: While the rate of SA's was generally comparable to the rate previously reported in PsO data, the small number of pregnancies among women with CD with prenatal exposure to UST precludes definitive interpretation of the data. In this case series, SAs were associated with older maternal age, and longer duration of UST exposure prior to the reported pregnancy was not associated with adverse outcomes. However, the limited available data from the UST CD program requires additional research to determine pregnancy and newborn safety. 1 Cather JC, Rahawi KW, Schaufelberger BW, Chan D, Horn EJ, Goyal K. Pregnancy outcomes in women exposed to ustekinumab in the psoriasis clinical development program. Journal of the American Academy of Dermatology . 2014;70(5). Funding Agencies: Janssen Research & Development, LLC funded this study